The Effect of Dextran of Various Molecular Weight on the Coagulation in Dogs - Bergentz, Sven Erik; Eiken, Oddvar; Nilsson, Inga Marie (Thrombosis and Haemostasis, 1961)
1. Infusions of low molecular weight dextran (Mw = 42 000) to dogs in doses of 1—1.5 g per kg body weight did not produce any significant changes in the coagulation mechanism.2. Infusions of high molecular weight dextran (Mw = 1 000 000) to dogs in doses of 1—1.5 g per kg body weight produced severe defects in the coagulation mechanism, namely prolongation of bleeding time and coagulation time, thrombocytopenia, pathological prothrombin consumption, decrease of fibrinogen, prothrombin and factor VII, factor V and AHG.3. Heparin treatment of the dogs was found to prevent the decrease of fibrinogen, prothrombin and factor VII, and factor V otherwise occurring after injection of high molecular weight dextran. Thrombocytopenia was not prevented.4. In in vitro experiments an interaction between fibrinogen and dextran of high and low molecular weight was found to take place in systems comprising pure fibrinogen. No such interaction occurred in the presence of plasma.5. It is concluded that the coagulation defects induced by infusions of high molecular weight dextran are due to intravascular coagulation.